Dampak Penggunaan Media Sosial Terhadap Hasil Belajar Geografi Siswa - Tifani, Andi Aulia (LaGeografia, 2019)
This study aims to: determine the intensity of social media usage on General High School students in Palopo City and find out the effect of social media usage on student geography learning outcomes. The variables in this study are the use of social media consisting of 4 indicators, namely 1) owned social media accounts, 2) intensity of accessing social media, 3) the use of social media, and 4) the impact of using social media. This type of research is quantitative descriptive. The population in this study were 2298 students and 10% of the samples were taken, 230 students. Sampling in this study using Simple random sampling technique. With. The results showed that 230 students taken in this study accessed social media in the highest frequency a day at> 5 hours a day, which was 61 students or 26.52% and from 6 schools studied only 3 schools where social media had an effect on learning outcomes the geography of students with a large influence of 10-15% with a weak degree of relationship, while the factors that cause social media to influence student learning outcomes come from internal and external factors of the students themselves. while the other 3 schools, where social media does not affect learning outcomes because they tend to use social media for the benefit of entertainment, friendship, online games, and others. Because the influence of the use of social media is weak and is only found in 3 schools, in this study Social Media has no effect on student geography learning outcomes.